Ziziphus jujuba Mill. var. spinosa (Bunge) Hu ex H. F. Chou Seed Ameliorates Insomnia in Rats by Regulating Metabolomics and Intestinal Flora Composition - Hua, Yue; Guo, Sheng; Xie, Hong; Zhu, Yue; Yan, Hui; Tao, Wei-wei; Shang, Er-xin; Qian, Da-wei; Duan, Jin-ao (Frontiers in Pharmacology, 2021)
The seed of Ziziphus jujuba Mill. var. spinosa (Bunge) Hu ex H. F. Chou (ZSS) is often used as a traditional Chinese medicine for insomnia due to its sedative and hypnotic effects, but the mechanism underlying this effect has not been thoroughly elucidated. In this study, an insomnia model induced by intraperitoneal injection of DL-4-chlorophenylalanine suspension in Sprague-Dawley rats was adopted to investigate the therapeutic effect of ZSS extract. Metabolomics analyses of plasma and urine as well as 16S rRNA gene sequencing of the intestinal flora were performed. The relationships between the plasma and urine metabolites and the intestinal flora in insomnia rats were also analyzed. The results showed that changes in plasma and urine metabolites caused by insomnia were reversed after administration of ZSS, and these changes were mainly related to amino acid metabolism, especially phenylalanine metabolism. The results of 16S rRNA gene sequencing and short-chain fatty acid determination showed that the ZSS extract could reverse the imbalance of intestinal flora caused by insomnia and increase the contents of SCFAs in feces. All of these improvements are mainly related to the regulation of inflammation. Therefore, it is concluded that insomnia, which alters metabolic profiles and the intestinal flora, could be alleviated effectively by ZSS extract.